Benchmark Analysis Of Heat Conduction Problems With Adaptive Fea Code Polyde - Jerome, Lee Jie Jen (Universiti Sains Malaysia, 2017)
Adaptive FEM is a topic of interest in research. As different implementations of research code have been developed, it is crucial to test the algorithms on benchmark problems so assessment of the performance can be done in a standard way. This work studies the performance of adaptive FEM code PolyDE on 3-dimensional steady-state heat transfer problem. PolyDE simulations were run for different adaptivity strategies with elements of different polynomial orders on curved surface and flat surface geometry domain. The adaptivity strategies studied were h-FEM and hp-FEM. H-FEM involves refining the mesh at the region where finer elements are required while hp-FEM involves combination of refining the mesh and changing the polynomial orders of the elements to improve the accuracy of the solution. Within the limitation of the number of degree of freedom tested, it was found that error for hp-FEM fits quadratic curves while the error for h-FEM fits linear line in logarithmic-logarithmic plot with respect to number of degree of freedom (NDOF) and CPU time (sec). The goodness of fits was proven with coefficient of determination,